Dual effects of acid etching on cell responses and mechanical properties of porous titanium with controllable open‐porous structure. Issue 6 (4th February 2020) - Wang, Dong; He, Guo; Tian, Ye; Ren, Ning; Liu, Wei; Zhang, Xianlong
Abstract: This study was focused on dual effects of 20 wt % hydrochloric acid etching treatment on cell responses and mechanical properties of a porous titanium with controllable open‐porous structure. The results show that the acid etching induced the formation of a rough surface on the porous titanium, resulting in a remarkable improvement of the MG‐63 osteoblasts adhesion and proliferation on the porous titanium. The surface roughness is found to be mainly dependent on the etching time. As increasing etching time, the surface roughness exhibited a noticeable rise. After etching for 90 min, the best cell response was achieved on the rough surface with a roughness value of 3.7 mm. However, the acid etching treatment displayed a negative effect on the porous titanium strength, and the yield strength was reduced down to 106 MPa as the etching time increased to 150 min. Taking both the cell responses and strength into account, an optimal etching time was determined as 60 min by experiments.